2005
DOI: 10.1124/dmd.105.006213
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Evaluation of the Metabolism and Bioavailability of Ester Prodrugs of Mgs0039 (3-(3,4-DICHLOROBENZYLOXY)-2-AMINO-6-FLUOROBICYCLO[3.1.0]HEXANE-2,6-DICARBOXYLIC Acid), a Potent Metabotropic Glutamate Receptor Antagonist

Abstract: ABSTRACT:MGS0039 (3-(3,4-dichlorobenzyloxy)-2-amino-6-fluorobicyclo-[3.1.0]hexane-2,6-dicarboxylic acid) has been identified as a potent and selective antagonist for metabotropic glutamate receptors. However, the oral bioavailability of MGS0039 is 10.9% in rats, due to low absorption. Several prodrugs, synthesized to improve absorption, exhibited 40 to 70% bioavailability in rats. This study investigated in vitro metabolism using liver S9 fractions from both cynomolgus monkeys and humans and oral bioavailabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…37,38 Group II mGluR antagonists have drawn attention as potential therapeutic compounds for the treatment of depression, anxiety and cognitive disorders. Inhibition of Group II mGluR in rodents enhances working memory, spatial learning and social recognition, 10,39 while also exhibiting acute and chronic antidepressant-like/anxiolytic effects.…”
Section: Resultsmentioning
confidence: 99%
“…37,38 Group II mGluR antagonists have drawn attention as potential therapeutic compounds for the treatment of depression, anxiety and cognitive disorders. Inhibition of Group II mGluR in rodents enhances working memory, spatial learning and social recognition, 10,39 while also exhibiting acute and chronic antidepressant-like/anxiolytic effects.…”
Section: Resultsmentioning
confidence: 99%
“…The basis for this therapeutic prediction comes from the convergent biologic effects of LY3020371 and that of ketamine, an NMDA receptor antagonist that produces rapid and persistent relief of depression symptoms in treatmentresistant depression patients (Zarate et al, 2006;Abdallah et al, 2015). Prior studies have also suggested the efficacy of mGlu2/3 receptor antagonists in depression (Chaki et al, 2004;Witkin and Eiler, 2006;Witkin et al, 2016a), and two mGlu2/3 antagonists have entered clinical development: BCI-838 (Yasuhara et al, 2006;Nakamura et al, 2006), an oral prodrug of orthosteric antagonist BCI-632, also known as MGS0039 (Nakazato et al, 2004;Yoshimizu et al, 2006) and RO4995819, also known as RG1538 (Decoglurant), an mGlu2/3 negative allosteric modulator (Gatti et al, 2006;clinicaltrials.gov, study NCT01457677).…”
Section: Discussionmentioning
confidence: 99%
“…As carboxyl groups can undergo deprotonation, molecules bearing carboxyl groups are usually negatively charged under physiological conditions, which makes them difficult to penetrate the negatively charged cell membrane. Many marketed drugs use simple esterification to enhace oral bioavailability and absorption in the treatment of many severe diseases, such as enalapril (an angiotensin-converting enzyme inhibitor), oseltamivir (an anti-influenza drug) and MGS0210 (a glutamate receptor antagonist)212223.…”
mentioning
confidence: 99%